If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3(6 + -1x) = 6 x + (6 * 3 + -1x * 3) = 6 x + (18 + -3x) = 6 Reorder the terms: 18 + x + -3x = 6 Combine like terms: x + -3x = -2x 18 + -2x = 6 Solving 18 + -2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -2x = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 6 + -18 -2x = 6 + -18 Combine like terms: 6 + -18 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| log(x+1)-log(x-1)=1 | | 4(6y)=0 | | a^2-3ab+2a-6b= | | (m^4n)^-5/m^-2n^4 | | 2/3a=4 | | -10x+2=-8x+8 | | x^2+1=x^2+2nx+n^2 | | 0.875x+14=-2x+9 | | (x+2)(x-1)=70 | | y=0.875x+14 | | y=-3/5*0+3 | | y=-3/5*-0.6+3 | | 35+140x=875 | | 3.4*0-2.3y=-8.2 | | y=-4*0-36 | | p=n+k+mforn | | 4x+x=80 | | 5x-2(x-8)=4+4x | | 141-6x=4 | | 4*0+3.7y=-8.5 | | 6x+8=105-5x | | 3(x-1)-15= | | -6*8+8y=-48 | | -6*-6+8y=-48 | | y=(x+1) | | 9+11x=12+x | | 7x-16=5x+14 | | y=0*-9+-9 | | y=0*0-9 | | 5+(-1)+7=30 | | 2+x=101 | | 5+7=30-x |